2015
DOI: 10.1007/s00296-015-3393-z
|View full text |Cite
|
Sign up to set email alerts
|

Lipid profile among girls with systemic lupus erythematosus

Abstract: The aim of the study was to describe biomarkers of lipid metabolism associated with increased cardiovascular risk and their correlation with disease variables and markers of inflammation in adolescent females with systemic lupus erythematosus (SLE). This cross-sectional controlled study evaluated 33 adolescent females with juvenile SLE and 33 healthy controls. Anthropometric data, SLE disease activity index (SLEDAI), medications, proteinuria, ultra-sensitive C-reactive protein (us-CRP), lipid profile (total ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 38 publications
2
12
0
1
Order By: Relevance
“…Our group has previously reported a high prevalence of dyslipidemia in children and adolescents with JIA and jSLE. [6][7][8][9] It is well established in the literature that dyslipidemia is a relevant factor for triggering the atherosclerotic process. 1 To our knowledge, this is the first study conducted in the pediatric population that describes the prevalence of dyslipidemia in individuals with JDM.…”
Section: Resultsmentioning
confidence: 99%
“…Our group has previously reported a high prevalence of dyslipidemia in children and adolescents with JIA and jSLE. [6][7][8][9] It is well established in the literature that dyslipidemia is a relevant factor for triggering the atherosclerotic process. 1 To our knowledge, this is the first study conducted in the pediatric population that describes the prevalence of dyslipidemia in individuals with JDM.…”
Section: Resultsmentioning
confidence: 99%
“…HDL in SLE also has abnormal proteomic features, with changes in Apo A‐I being the most noteworthy. In the study by Machado et al, female adolescents with SLE had a higher ratio of HDL cholesterol to Apo A‐I compared to healthy controls, indicating that the HDL particles in those SLE patients had a lesser amount of Apo A‐I . Juárez‐Rojas et al reported lower Apo A‐I and higher Apo E content in HDL particles isolated from women with SLE .…”
Section: Changes In Hdl Composition In Sle Patientsmentioning
confidence: 96%
“…Reduced ApoA1 and reduced HDL concentration have been reported previously in JSLE patients compared with healthy donors [43] and increased Apo-B was associated with arterial stiffness in adult SLE patients [44].…”
Section: Discussionmentioning
confidence: 55%